On analysis of trust dynamics in supply chain collaboration - Daudi, Morice; Hauge, Jannicke; Thoben, Klaus-Dieter (International Conference on Information Systems, 2024)
Paper published in Proceedings of the 6th International Conference on Information Systems, Logistics and Supply Chain, ILS 2016